Asymptotic investigation into linear hamiltonian differencial systems of the statics of elastic shells of revolution - Kireev, Igor Valerievich; Nemirovskii, Yuriy Vladimirovich (Computational Continuum Mechanics, 2011)
We propose a method of constructing the asymptotic approximations to the solution of the governing equations of linear theory of shells of revolution in complex Hamiltonian form. Based on the Wasow approach, an algorithm for constructing symplectic transformations of the original system of linear differential equations in the canonical form is developed. Asymptotic expansions for the solutions of linear Hamiltonian differential systems of the statics of the shell of revolution are constructed.
Keywords: elasticity; theory of shells; Hamiltonian system; asymptotic analysis